PROBLEMS AND SOLUTIONS OF ECONOMICS (Analysis of International Sciences, 2023)
In this article, the emergence of the digital economy, the world economy and the importance of digital technologies in the life of society, the development of digital platforms, advantages and disadvantages of the digital economy have been analyzed. Based on the analysis, some proposals have been developed to eliminate existing problems.